KAJIAN SISTEM JURNAL VOUCHER DENGAN MENGGUNAKAN PERANGKAT LUNAK ERP SAP R/3 UNTUK MODUL REPORT AKUNTANSI KEUANGAN PADA PT. XYZ - ACHMAD SARWANDIANTO (Faktor Exacta, 2013)
One of the keys to success for companies to remain superior in global competition is the decision-making right and at the right time. To support this, the decision makers need accurate information and real-time. By using the method of grounded, this research can be perfect, because it can take the completeness of the data or information directly on the XYZ Company. In its application, SAP software is not easy to directly use due to business processes in every company is different – different, but did not close the possibility to configure the SAP so that the application can customize an existing business process. For example the menu additions case Report Journal Vouchers in Financial Accounting module Asyst and Controlling Department in pt. XYZ. Analyze make good data processing and result reporting in accordance with the needs that exist. Starting from analyzing business processes which run in PT XYZ Indonesia along with the existing constraints, it is recommended to use the SAP software PT XYZ with the concept of ERP (Enterprise Resources Planning) so that any existing processes can be connected to each other so that PT XYZ Company can implement in a more efficient, effective and transparan. Keyword: ERP, SAP, reporting